Monitoring of the brown stink bug Euschistus heros (Hemiptera: Pentatomidae) with sex pheromone in soybean fields - Silva, Valvenarg Pereira da; Pereira, Mônica Josene Barbosa; Vivan, Lúcia Madalena; Blassioli-Moraes, Maria Carolina; Laumann, Raúl Alberto; Borges, Miguel (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the efficiency of rubber septum and lure formulations of the brown stink bug Euschistus heros sex pheromone and to compare it with the shake cloth method for monitoring this pest in soybean fields. The treatments were: pheromone in rubber septum, pheromone in lure, and sampling with shake cloth. Samples were taken weekly during the soybean reproductive stage (ten weeks). To estimate bug population density and compare it with the capture in pheromone traps, four shake clothes per week were carried out in all plots; in addition, the number of bugs captured in traps was determined weekly. Damage caused by bugs in seeds was evaluated using the tetrazolium test. Pheromone formulations were effective in capturing E. heros, and the lure formulation captured more bugs. Early population control, indicated by the level of control in the pheromone traps, resulted in seeds with higher quality than those from plots monitored with shake cloth. Therefore, pheromone traps are more efficient than the shake cloth for monitoring stink bug populations during the critical phase of the bug attack in soybean fields.